PENGARUH GAYA KEPEMIMPINAN SITUASIONAL DAN KAPASITAS PEGAWAI TERHADAP KINERJA PEGAWAI PADA DINAS PERTANIAN TANAMAN PANGAN DAN HORTIKULTURA PROVINSI LAMPUNG - . Karyawati (Universitas Bandar Lampung (UBL), 2016)
Dinas Pertanian Tanaman Pangan dan Hortikultura is one of the areas that is supporting the task of head area which is led by a head of department, responsible to the governor through secretary, in charge of carrying out the affairs of Government in the field of agriculture. This research aims to analyze the factors that affect the performance of employees by the number of samples 44 people from all clerk Dinas Pertanian Tanaman Pangan dan Hortikultura Provinsi Lampung.This research aims to find out how the influence of situational leadership style and capacity of employees on performance clerk at the Dinas Pertanian Tanaman Pangan dan Hortikultura Provinsi Lampung. In this study the author using qualitative and quantitative data analysis. As for the technique of collecting data in this study are: observation, questionnaires and documentation.Based on the processing of the data, in general the results of this research are as follows: (1) Situational leadership style has a positive influence on performance clerk in the Dinas Pertanian Tanaman Pangan dan Hortikultura Provinsi Lampung it is visible from the correlation coefficient test results showed that the leadership style of situsional with the performance of the employees of the Dinas Pertanian Tanaman Pangan dan Hortikultura Provinsi Lampung has the direction of the positive correlations and relationships both within the category of very high. (2) the capacity of the Employee has a positive influence on performance clerk in the Dinas Pertanian Tanaman Pangan dan Hortikultura Provinsi Lampung, it terlihar of the correlation coefficient test results showed that the capacity of the employee with the employee's performance in the Dinas Pertanian Tanaman Pangan dan Hortikultura Provinsi Lampung has the direction of the positive correlations and relationships both within the category of very high. (3) the style of leadership and a capacity of situsional employees on performance clerk has a strong and positive influence so that it can be drawn the conclusion that if the leadership style of situsional and the capacity of employees is not implemented properly then it will degrade the performance of employees. Keywords: Situational Leadership Styles, Employee Performance, Capacity